(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to describe the physical activity of students who use gadgets through an analysis of three related scientific articles. Increased gadget use has the potential to reduce students’ physical activity and fitness. This study uses a literature study approach by searching various scientific sources through Google Scholar using the keyword "physical activity of gadget users." From the search results, three scientific articles published between 2019 and 2024 were obtained and deemed relevant to the research focus. The three articles were analyzed in depth to examine the research methods, findings, and implications of the relationship between gadget use and physical activity in students. The results of the study indicate that a high duration of gadget use is correlated with low physical activity in students, while good management of gadget use time has an impact on more optimal physical activity. This study emphasizes the importance of efforts to regulate technology use to prevent the reduction of students’ health and physical fitness.